Economic Analysis of Corn Plantation Factors Using Geographic Information System Through Location Quotient and Shift Share Method in East Java Province - Koni Dwi Prasetya; Wahyu Fistia Doctorina ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2023)
Agriculture is the largest sector in almost every developing country economy, such as a corn plantation. This sector provides food for the majority of its population, provides employment for almost all of the existing workforce, produces raw materials, or aids for the industry and becomes the largest source of foreign exchange earnings comparison between cities and another. So that agriculture is needed in a region one of them is East Java Province. In the development of the Area, especially in fulfilling the food needs through agriculture and plantation, it needs analysis based on region and its production. One method through Location Quotient (LQ) analysis through this method can be known base sector in a region compared to other regions. After that to know the growth of agricultural production of a sector used Shift Share analysis method. The data used are by BPS on agriculture and plantation category in East Java in 2012 until 2016.